Answer:
x = 1
Explanation:
Please express exponentiation using the symbol " ^ " : x^2 - 8x + 7 = 0
Let's solve this equations using "completing the square:"
x^2 - 8x + 7 = 0
1) Identify the coefficient of the x term. Here it's -8.
2) take half of that and square it: we get (-4)² = 16
3) insert " +16 - 16 " between the 8x and the 7:
x^2 - 8x + 16 - 16 +7 = 0
4) Rewrite this perfect square:
(x - 4)² - 16 + 7 = 0 -> (x - 4)^2 = 9
5) Solve for (x -4) by taking the square root of both sides:
x - 4 ± sqrt(9) -> x - 4 ± 3
6) Solve for x: x = 4 ± 3, or x = 7 and x = 1.
7) Take the lesser root of 7 and 1. That would be x = 1. Answer B is correct.